Factoring sociolinguistic variation into the history of Indo-Portuguese - Cardoso, Hugo C. (2014)
Given that the Portuguese-lexified creoles of South Asia are currently spoken by relatively small and close-knit communities, it is often assumed that little sociolinguistic variation will be found within them and/or that this must have been the case throughout their history. This article, however, explores how modern and earlier (18th-/early-20th-century) descriptions and commentaries on the Indo-Portuguese communities reveal a somewhat stratified linguistic repertoire not unlike that of various other creoles around the world. Based on a survey of sources of different periods and character, I argue that there is good reason to assume a considerable degree of sociolinguistic variation in the IndoPortuguese communities even when the available sources do not record it, and that failure to do so may compromise the validity of our linguistic studies.